2021
DOI: 10.1186/s12909-021-02710-y
|View full text |Cite
|
Sign up to set email alerts
|

A Q-method approach to perceptions of professional reasoning in occupational therapy undergraduates

Abstract: Background Professional reasoning provides a firm basis for the development of teaching and assessment strategies to support the acquisition of skills by healthcare students. Nevertheless, occupational therapy educators should use diverse methods of learning assessment to examine student learning outcomes more fully with an evaluation that supports the overall complexity of the process, particularly learners’ subjective experience. The aim of this article is to identify the range of perspective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
0
0
Order By: Relevance
“…53(2) 88-93 DOI: 10.24425/ppb.2022 symptoms of burnout in different professional groups (Bochelyuk et al, 2007;Bochelyuk, 2010;Bochelyuk et al, 2016a;Bochelyuk et al, 2016b). Preliminary analysis of the category of professional personality crises from a scientific perspective showed that the construct "professional self-determination" positions the individual not only as a subject of labour, but also as a subject of being in various conditions of life (Hu, 2021;Priyadi et al, 2021;Cobos & González, 2021;Márquez-Álvarez et al, 2021).…”
Section: Original Papersmentioning
confidence: 99%

Polish Psychological Bulletin

Bocheliuk,
Spytska,
Shaposhnykova
et al. 2022
“…53(2) 88-93 DOI: 10.24425/ppb.2022 symptoms of burnout in different professional groups (Bochelyuk et al, 2007;Bochelyuk, 2010;Bochelyuk et al, 2016a;Bochelyuk et al, 2016b). Preliminary analysis of the category of professional personality crises from a scientific perspective showed that the construct "professional self-determination" positions the individual not only as a subject of labour, but also as a subject of being in various conditions of life (Hu, 2021;Priyadi et al, 2021;Cobos & González, 2021;Márquez-Álvarez et al, 2021).…”
Section: Original Papersmentioning
confidence: 99%

Polish Psychological Bulletin

Bocheliuk,
Spytska,
Shaposhnykova
et al. 2022